Passage through hell : modernist descents, medieval underworlds - Pike, David L. (David Lawrence), 1963- (Cornell University Press, 1997)
Taking the culturally resonant motif of the descent to the underworld as his guiding thread. David L. Pike traces the interplay between myth and history in medieval and modernist literature. Passage through Hell suggests new approaches to the practices of comparative literature, and a possible escape from the current morass of competing critical schools and ideologies.
Keywords: Hell in literature.; Literature -- History and criticism.; Civilization, Medieval, in literature.; Modernism (Literature); Enfer dans la littérature.; Littérature -- Histoire et critique.; Civilisation médiévale dans la littérature.; Modernisme (Littérature); BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Civilization, Medieval, in literature; Hell in literature; Literature; Höllenfahrt -- Motiv; Literatur; Letterkunde.; Hel.; Geschichte 1500-1990.; Criticism, interpretation, etc.